2020
DOI: 10.1001/jamanetworkopen.2020.19176
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Bronchoscopic, and Imaging Findings of e-Cigarette, or Vaping, Product Use–Associated Lung Injury Among Patients Treated at an Academic Medical Center

Abstract: IMPORTANCE e-Cigarette, or vaping, product use-associated lung injury (EVALI) has caused more than 2800 illnesses and 68 deaths in the United States. Better characterization of this novel illness is needed to inform diagnosis and management. OBJECTIVE To describe the clinical features, bronchoscopic findings, imaging patterns, and outcomes of EVALI. DESIGN, SETTING, AND PARTICIPANTS This case series of 31 adult patients diagnosed with EVALI between June 24 and December 10, 2019, took place at an academic medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 52 publications
3
64
0
5
Order By: Relevance
“…Given the deleterious effects of e-cigarette use on lung function, 12 it is possible that even if e-cigarette use does not increase the risk of developing infection, it could still increase the severity of disease, as may be the case for conventional cigarettes. 2 Although e-cigarettes have the well-documented potential for harm, 13,14 and the COVID-19 pandemic presents an opportunity to reduce e-cigarette use, [15][16][17] our study found that such use does not appear to increase susceptibility to SARS-CoV-2 infection among patients seeking medical care. This result suggests the hypothesis that any effects of conventional cigarette smoking on susceptibility are not mediated by nicotine.…”
Section: Discussionmentioning
confidence: 53%
“…Given the deleterious effects of e-cigarette use on lung function, 12 it is possible that even if e-cigarette use does not increase the risk of developing infection, it could still increase the severity of disease, as may be the case for conventional cigarettes. 2 Although e-cigarettes have the well-documented potential for harm, 13,14 and the COVID-19 pandemic presents an opportunity to reduce e-cigarette use, [15][16][17] our study found that such use does not appear to increase susceptibility to SARS-CoV-2 infection among patients seeking medical care. This result suggests the hypothesis that any effects of conventional cigarette smoking on susceptibility are not mediated by nicotine.…”
Section: Discussionmentioning
confidence: 53%
“…The DAH pattern was defined as patchy or multifocal GGO, consolidation, or both with superimposed acinar ground-glass centrilobular nodules (CNs) filling most of the secondary lobule. 9,11,19,20 Unlike other patterns, DAH could be asymmetrical. All patients with a DAH pattern had to have either bronchoscopic confirmation of DAH or witnessed hemoptysis.…”
Section: Take-home Pointsmentioning
confidence: 94%
“…Patients with EVALI presented leukocytosis, elevated erythrocyte sedimentation rate, and high C-reactive protein levels in peripheral blood. The BALF showed a predominance of macrophages and neutrophils; chest radiography revealed multifocal, multilobar opacities, variable in extent and distribution, consistent with foci of alveolar consolidation [ 82 ], with the presence of vitamin E acetate in some reports [ 83 ]. The most frequent clinical presentation included shortness of breath, cough, chest pain, gastrointestinal symptoms such as abdominal pain, nausea, and vomiting, and neurologic symptoms including headache, lethargy, and confusion [ 84 ].…”
Section: Resultsmentioning
confidence: 78%